Panel Data Analysis of Regulatory Factors Shaping Environmental Performance - Earnhart, Dietrich (The Review of Economics and Statistics, 2004)
This paper analyzes the regulatory factors shaping environmental performance at individual polluting facilities. In particular, it examines the influence of actual government interventions, namely, inspections and enforcement actions performed at specific facilities. This influence represents specific deterrence. This paper also examines general deterrence, that is, the threat of receiving an intervention. As important, it controls for differences in certain regulatory features of facility-specific pollution control permits. Unlike previous attempts to examine regulatory factors, this analysis uses panel data techniques to capture the heterogeneity across individual facilities, while exploring the dynamics of each facility; the analysis also captures heterogeneity across individual time periods.